2017
DOI: 10.1530/ec-17-0243
|View full text |Cite
|
Sign up to set email alerts
|

Myo-inositol effects in women with PCOS: a meta-analysis of randomized controlled trials

Abstract: Myo-inositol (MI) supplementation in women with polycystic ovary syndrome (PCOS) has been evaluated over the last years. Many hormonal and reproductive impairments associated with this disorder seem relieved by the supplement. The objective of the meta-analysis was to assess the effects of MI alone or combined with d-chiro-inositol (DCI) on the endocrine and metabolic abnormalities of women with PCOS. Literature was retrieved from selected databases, MEDLINE, EMBASE, PubMed and Research Gate (up to November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 88 publications
3
82
0
4
Order By: Relevance
“…4,5 Furthermore, and like that seen with metformin administration, endocrine and metabolic parameters in PCOS also seem to be altered in favorable ways by myoinositol, the most abundant inositol isomer. 6 We fully agree with Levin and Rottenstreich that the documentation on inositol isomers for ovulation induction in PCOS is scarce and that large randomized controlled trials are greatly needed. Such studies seem to be under way.…”
supporting
confidence: 72%
“…4,5 Furthermore, and like that seen with metformin administration, endocrine and metabolic parameters in PCOS also seem to be altered in favorable ways by myoinositol, the most abundant inositol isomer. 6 We fully agree with Levin and Rottenstreich that the documentation on inositol isomers for ovulation induction in PCOS is scarce and that large randomized controlled trials are greatly needed. Such studies seem to be under way.…”
supporting
confidence: 72%
“…Another recent meta-analysis [ 48 ] examined 9 randomized controlled trials (RCTs) on PCOS women (247 cases and 249 controls) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The authors evaluated the efficacy of supplementing MI alone, or in association with DCI in the 40:1 ratio, considering fasting insulin concentrations as the primary outcome, while HOMA index and serum levels of testosterone, androstenedione and sex hormone-binding globulin (SHBG) as secondary.…”
Section: Inositol-based Pcos Managing: the 40:1 Mi/dci Formulamentioning
confidence: 99%
“…Inositol has two major stereoisomers: myo-inositol (MYO) and Dchiro-inositol (DCI). MYO supplements have been observed to improve the metabolic profile and hyperandrogenism of women with PCOS [4,5], in addition to increasing the clinical pregnancy rate in infertile women undergoing ovulation induction for ICSI or IVF-ET, probably improving the quality of embryos and reducing the number of unsuitable oocytes [6]. However, a recent systematic review showed that MYO supplementation is not sufficient to improve oocyte maturation, embryo quality or the pregnancy rate [7].…”
Section: Introductionmentioning
confidence: 99%